Determinants of the Realization of Second Chance Education - Lenka Pasternáková; Silvia Barnová; Miron Zelina; Slávka Krásna; Gabriela Gabrhelová (Emerging Science Journal, 2023)
The aim of the study is to present a newly developed research instrument examining the determinants of second chance programmes' success or failure from the perspective of teachers. In the theoretical part of the study, the authors elaborate on the issues of second chance education and focus on factors having a direct impact on the results of its realization. Subsequently, the Second Chance Education Indicators Questionnaire developed by the authors, the results of the carried out internal factorial analysis, as well as the calculated correlations, are presented. Based on the gathered data from 1,038 teachers, seven factors – "Satisfying employers' needs in the field of education"; "Promoting the development of teachers' competencies for second chance education"; "Providing teachers with support in developing their professional skills in the field of second chance education"; "Funding schools providing second chance education"; "The system of dual VET in second chance education"; and "Potentials for increasing the quality of second chance education" – were identified, and the existence of an internal factorial structure was confirmed. Since there is no other available research tool for identifying these determinants, it can be assumed that the Second Chance Education Indicators Questionnaire is a unique research tool, which can be used for further research activities and can contribute to broadening the current knowledge in the field. Doi: 10.28991/ESJ-2023-SIED2-015 Full Text: PDF